HUBUNGAN DUKUNGAN SUAMI DAN SOSIAL EKONOMI DENGAN MINAT PENGGUNAAN KONTRASEPSI METODE OPERASI WANITA (MOW) PADA PASANGAN USIA SUBUR (PUS) DI RUMAH SAKIT AISYIYAH KUDUS - Anik Suryani; Ana Zumrotun Nisak; Dwi Astuti (Rena Cipta Mandiri, 2026)
Female surgical contraception (FSC) is an effective method of contraception that reduces birth rates. The choice of contraception is influenced by several factors, one of which is the support of the husband. In addition to spousal support, an individual's ability to choose contraception is also based on cost considerations. This study aims to analyse the relationship between spousal and socioeconomic support and interest in using female surgical contraception (FSC) among couples of reproductive age (CRA). This study used an analytical correlation approach. The population of this study consisted of all patients who used contraception at Aisyiyah Kudus Hospital, totalling 85 patients. The sample required in this study was 71 respondents. The instruments used were a husband support questionnaire, a socio-economic questionnaire, and a questionnaire on interest in using MOW. Statistical analysis used the Spearman rank test with a significance level of 5% (0.05). A total of 45 (63.4%) received support from their husbands, 39 (54.9%) had an income equal to or above the minimum wage, and respondents had a high interest in using MOW contraception, namely 50 (70.4%). There is a relationship between spousal support (0.000) and socioeconomic status (0.003) with interest in using the female surgical contraceptive method (MOW) among couples of reproductive age (PUS) at Aisyiyah Hospital in Kudus.